KOMPETENSI TUTOR DALAM PELAKSANAAN PEMBELAJARAN KEJAR PAKET C PADA MASA PANDEMI COVID-19 DI UPT SKB CERME, GRESIK - Kusuma, Elsa Mega (J+PLUS UNESA, 2021)
The Covid-19 pandemic in Indonesia has an impact on all parties, especially in the world of education. The government makes policies for all lines of education to carry out the learning process online. This policy requires tutors to be technologically literate and improve the competence of the tutor. The competencies that must be developed are pedagogikal competence and tutor professional competence in order to support the successful implementation of chase learning package C at UPT SKB Cerme, Kab. Gresik. The purpose of this study was to determine the pedagogikal competence and professional competence of tutors in implementing the package C equivalency program learning during the Covid-19 pandemic at UPT SKB Cerme, Kab. Gresik. The method used in this research is descriptive quantitative survey method. This study uses a closed questionnaire in the form of statements distributed via google form. The research respondents were 22 tutors for package C equivalency at UPT SKB Cerme Kab. Gresik. Respondents of the study gave responses presented in percentage diagram form. The results of this study indicate that the pedagogikal competence and professional competence possessed by the tutor show good results, it can be seen in the pedagogikal variables showing that, the tutor is able to understand students well, the tutor makes lesson planning plans, the tutor implements the learning process well, the tutor is able to design and carry out learning evaluations, and tutors can develop students to actualize various potentials. The professional competency variable shows the tutor is able to master the learning material, the tutor is able to open learning well, the learning carried out by the tutor is very varied, able to manage the class well and the tutor has the accuracy between time and learning material well.